Changes in and correlates of cannabis-involved substance use treatment admissions age 50 and older, 2000–2021 - Choi, Namkee G.; Marti, C. Nathan; Choi, Bryan Y. (Frontiers in Public Health, 2025)
Background and aimsCannabis use among U.S. older adults has risen rapidly over the past two decades. This study examined the changes in and correlates of cannabis-involved substance use treatment admissions among this demographic.MethodsUsing the 2000–2021 concatenated Treatment Episode Data Set-Admissions (TEDS-A) age 50+ (N=5,593,004), we fitted joinpoint regression models to examine changes in the percent of cannabis-involved admissions of all substance use admissions. We used multinomial and binary logistic regression models to examine the demographic and treatment-related correlates of cannabis-primary admissions and cannabis-secondary/tertiary admissions.ResultsDuring the study period, the number of cannabis-involved admissions increased substantially, while their share of all admissions increased and then decreased as other drug-related admissions increased. The annual percentage changes (APC) show that the shares of cannabis-involved admissions of all admissions between 2000 and 2012 increased for the 50–64 age group and then decreased between 2012 and 2021. In the 65+ age group, the shares increased between 2000 and 2016 (APC=5.2) and then plateaued. Compared to no-cannabis admissions, the likelihood (relative risk ratio) of all cannabis-involved admissions was higher among males, black people, residents of states where medical or recreational cannabis use was legal, and referrals from healthcare providers and court/criminal legal systems. The likelihood (adjusted odds ratio [AOR]) of cannabis-primary admissions was higher among those age 65+ (aOR=1.04, 95%CI=1.00–1.08), black people (aOR=1.34, 95% CI=1.32–1.36), Hispanic people (aOR=1.26, 95% CI=1.23–1.29), residents of states with medical cannabis laws, and those who were referred by healthcare providers and legal systems.ImplicationsCannabis-involved admissions are projected to continue to increase as cannabis use continues to increase. More effective regulations and enforcement of delta-9-tetrahydrocannabinol potency and research on cannabis harms and poly-substance use are needed to protect the health of older adults who turn to cannabis for its purported health benefits. Increased availability and accessibility of treatment infrastructure are also needed.